The German Energiewende under attack: Is there an irrational Sonderweg? - Erik Gawel; Sebastian Strunz; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
The German energy transition repeatedly faces harsh critiques questioning its economic and environmental merit. This article defends the Energiewende and argues that Germany has chosen a rational and particularly forceful approach to securing sustainable energy supply. Though current expenditures are high, the long-run benefits of transforming the energy system to a renewables-based system are likely to outweigh present investment costs. Furthermore, support policies for renewables are not redundant - as some critics claim - but complement other policy instruments, such as the emissions trading scheme. The article also addresses the motives behind the discrediting attacks on the German energy policy regime. Defense actions by beneficiaries of the former energy market structure are only to be expected, but the attacks from liberal economists are astonishingly fierce.
Keywords: D62; H54; Q42; Q48; Q53; Q54; 330; energy supply; energy transition; externalities; Germany; renewable energy sources; support policies; sustainability